Vertical geomediation: The automation and platformization of photogrammetry. (November 2022) - Wilken, Rowan; Thomas, Julian
Photogrammetry is the science of using photographs to make measurements and derive three-dimensional (3D) data about objects or terrain from two-dimensional (2D) imaging. In this article we view photogrammetry through the lens of geomedia studies, arguing two things. First, we suggest the accumulation and concentration of photogrammetric capabilities, technologies and knowledge, from the First World War onwards can be understood as both part of the 20th-century creation of a 'government machine', and a crucial element within the longer-run 'cartographic project'. Through both world wars and the post-war period, aerial photogrammetry emerged as a fundamental capability for government-supported geomedia infrastructure and spatial information capture – what we term an extended geomedia infosphere. Second, we examine the critical dynamics of digitization, automation and platformization. These developments, we argue, have led to a redistribution of photogrammetric capabilities and technologies outside governmental cartography, with implications for platforms and geomedia studies.